Meningitis caused by Neisseria Meningitidis, Hemophilus Influenzae Type B and Streptococcus Pneumoniae during 2005-2012 in Turkey A multicenter prospective surveillance study - Ceyhan, Mehmet; Gurler, Nezahat; Ozsurekci, Yasemin; Keser, Melike; Aycan, Ahmet Emre; Gurbuz, Venhar; Coskun, Yavuz (Taylor & Francis Inc, 2014)
Successful vaccination policies for protection from bacterial meningitis are dependent on determination of the etiology of bacterial meningitis. Cerebrospinal fluid (CSF) samples were obtained prospectively from children from 1 month to <= 18 years of age hospitalized with suspected meningitis, in order to determine the etiology of meningitis in Turkey. DNA evidence of Neisseria meningitidis (N. meningitidis), Streptococcus pneumoniae (S. pneumoniae), and Hemophilus influenzae type b (Hib) was detected using multiplex polymerase chain reaction (PCR). In total, 1452 CSF samples were evaluated and bacterial etiology was determined in 645 (44.4%) cases between 2005 and 2012; N. meningitidis was detected in 333 (51.6%), S. pneumoniae in 195 (30.2%), and Hib in 117 (18.1%) of the PCR positive samples. Of the 333 N. meningitidis positive samples 127 (38.1%) were identified as serogroup W-135, 87 (26.1%) serogroup B, 28 (8.4%) serogroup A and 3 (0.9%) serogroup Y; 88 (26.4%) were non-groupable. As vaccines against the most frequent bacterial isolates in this study are available and licensed, these results highlight the need for broad based protection against meningococcal disease in Turkey.
Keywords: Meningitis; Turkey; etiologic agents; N. meningitidis; S. pneumoniae; Hib; epidemiology; surveillance